Reconstructing Lost Instruments: Praetorius’s Syntagma musicum and the Violin Family c. 1619 - Matthew Zeller (De Musica Disserenda, 2019)
Michael Praetorius’s De organographia and Theatrum instrumentorum provide valuable clues that contribute to a new understanding of the violin family c. 1619, many surviving examples of which are reduced in size from their sixteenth- and seventeenth-century dimensions. The record of surviving instruments – especially those of the Amati family – alongside metrologic, documentary and iconographic evidence shows that Michael Praetorius describes a large instrument conforming remarkably well to the original dimensions of the basso da braccio (violoncello), as well as furnishing an excellent scale representation of the violin family as it was at the time of these works’ publication and an accurate tuning scheme.